Incentive Distribution of Specialist Doctors in Government General Hospital - Andi Leny Susyanty; Harimat Hendarwan; Amir Su'udi (Jurnal Penelitian dan Pengembangan Pelayanan Kesehatan, 2020)
Abstract Maintaining and fulfilling the needs of specialist doctors in government public hospitals is still a challenge. Government general hospitals have not been able to meet the minimum standard for specialist doctors. The distribution of personnel and the incentives received by specialist doctors varies between regions. This study aims to provide recommendations related to policies to meet the needs of specialist doctors at government general hospitals. This cross-sectional research study was conducted in May - December 2017 in 19 hospitals in 18 districts/cities. A total of 134 specialist doctors and dental specialists were respondents in this study. The fulfillment of non-financial incentives for specialist doctors, 28.4% lived in official homes, 41.8% received official vehicles and 73.1% were facilitated to attend seminars/education and training. Fulfillment of financial incentives shows that 73.1% of their income is sufficient for the family’s needs for 1 month and 63.5% can save. Further east, the incentives received by specialist doctors are greater. The combined capacity of central and local budgets can be optimized to provide adequate and equitable incentives to retain specialist doctors in government hospitals, especially in less desirable areas and with limited budgets. Keywords: adequacy, disparity, incentive Abstrak Keberadaan dan kecukupan dokter spesialis di rumah sakit umum pemerintah masih menjadi kendala. Masih banyak rumah sakit yang belum memenuhi standar minimal dokter spesialis di rumah sakit dan masih adanya disparitas distribusi tenaga dan insentif dokter spesialis di tiap daerah. Penelitian ini bertujuan untuk menyediakan rekomendasi kebijakan terkait pemenuhan kebutuhan dokter spesialis dari aspek penyediaan insentif bagi dokter. Penelitian ini dilakukan secara cross-sectional dan dilaksanakan pada bulan Mei - Desember 2017 di 19 RS di 18 kabupaten / kota. Sebanyak 134 dokter spesialis dan dokter gigi spesialis yang menjadi responden penelitian ini. Sebanyak 28,4% tinggal di rumah layanan yang disediakan, 73,1% dari pendapatannya mencukupi kebutuhan keluarga selama 1 bulan, 63,5% dapat menabung, 41,8% dapat kendaraan, 73,1% telah difasilitasi untuk mengikuti seminar / pendidikan dan pelatihan. Semakin ke timur, insentif yang diterima dokter spesialis semakin besar. Kombinasi kemampuan anggaran pusat dan daerah dapat dioptimalkan untuk memberikan insentif yang memadai dan merata untuk mempertahankan dokter spesialis di rumah sakit pemerintah, terutama di daerah yang tidak diminati dan dengan kendala anggaran. Kata kunci: kecukupan, disparitas, insentif